Breast Self - examination Predictors based on Precede Model: a study on female active health volunteers in Zarand City - Hakimeh Khaleghi Mahani; Fadakar Mohammad Mehdi; Ahmadi Tabatabaei Seyed Vahid; Mirzai Moghadameh; Poursharifei Abbas (Kerman University of Medical Sciences, 2017)
Background & Objectives: Breast cancer is still the most common malignancy leading to women mortality worldwide and late diagnosis of breast cancer is still one of the main causes of death in affected women. One of the ways of early detection of breast cancer is breast self - examination. The aim of this study was to determine predicting factors of breast self - examination in female active health volunteers of Zarand/ Iran based on Precede model. Methods: In this descriptive- analytical study, all participants of active heath volunteer program in health centers of zarand (110 women) were recruited. Data were collected using a researcher - made questionnaire consisted of two sections of demographic information and constructs of Precede model. Data were analyzed through SPSS22 and by using descriptive statistics (distribution and central tendency, frequency and percent) and analytic statistics (logistic regression). Results: Mean age of participants was 37.76 ± 9.75 years and 81.8 % of them were married. Among Precede constructs, predisposing factors (self-efficacy: OR=1.46 and knowledge: OR=1.30) had the highest predicting role. Performing breast self - examination showed significant relationship with level of education (OR=0.01), family history of breast cancer (OR=0.02) and marital status (OR=0.04). Conclusion: Since predisposing factors were the most important predicting factors for breast - self-examination, in planning health education programs, more attention should be paid to improving women's self - efficacy and increasing their awareness about breast self - examination. Keywords: Breast Self - Examination, Precede Model, Predicting, Health Volunteers Citation: Khaleghi Mahani H, Fadakar MM, Ahmadi Tabatabaei SV, Mirzai M, Poursharifei A. Breast Self - examination Predictors based on Precede Model: a study on female active health volunteers in Zarand City. Journal of Health Based Research 2017; 3(1): 71-85.